Consumers knowledge and perception towards Melicope ptelefolia (Daun Tenggek Burung): a preliminary qualitative study - Abdul Karim, Muhammad Shahrim; Nasouddin, Siti Safrina; Othman, Mohhidin; Mohd Adzahan, Noranizan; Hussin, Siti Rahayu; Shaari, Khozirah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Melicope ptelefolia (MP) is one of the alternative herbal resources which have a great potential to be marketed worldwide. Because of its exploratory nature, this study used qualitative research methodology, which is natural and highly interpretive in order to gain consumer insights. This preliminary qualitative study used an in-depth personal interview approach for data collection. Informants for this study were 30 regular consumers of MP, aged from 18 years old and above. From the findings, it is reported that MP had a slightly bitter taste, crunchy young leaves, pungent, and lemon-lime aroma. In terms of its physical characteristics, it is said that MP has trifoliate, green, thick, broad leaves and has small white and greenish flowers. Respondents have varying levels of awareness and knowledge regarding MP but most of them believed that medicinal products can be produced from this herb. Respondents also stressed the importance of scientific research to properly develop MP into medicinal products and turn it into alternative treatment that has commercial values in the market.